Effect of Sudarshan Kriya Pranayama on periodontal status and human salivary beta-defensin-2: An interventional study - R Ananthalakshmi; Jaideep Mahendra; P Jayamathi; Little Mahendra; Nashra Kareem; S Subramaniam (Wolters Kluwer Medknow Publications, 2018)
Background: Yogic stretching (asana) has been proven to have an effect on salivary human beta-defensin-2 (HBD-2) concentration, which is an antimicrobial peptide and is an inflammatory marker in periodontal disease. Sudarshan Kriya Pranayama (SKP) is a part of yoga which involves rhythmic breathing. Hence, we aim to evaluate the periodontal parameters and to estimate the salivary HBD-2 level before and after SKP program in periodontitis individuals. Materials and Methods: An interventional study was designed and individuals were divided into three groups: Group I - healthy periodontium, Group II - chronic gingivitis, and Group III - chronic periodontitis. SKP was the interventional tool. The clinical parameters such as plaque index (PI), gingival index (GI), probing pocket depth (PPD), clinical attachment level (CAL), and salivary HBD-2 level were analyzed at baseline and 90 days after the SKP practice. Enzyme-linked immunosorbent assay (ELISA) was used to evaluate salivary HBD-2. McNemar's Chi-square, Paired samples t-test, and one-way ANOVA were used to analyze the results. P < 0.05 was considered statistically significant. Results: Following the SKP intervention, the clinical parameters such as PI and GI improved significantly in all the groups (P < 0.001); however, Group III showed a significant reduction as compared to the other groups. The mean baseline salivary HBD-2 levels of Group I, Group II, and Group III were 91.78 ng/μl, 110.22 ng/μl, and 157.63 ng/μl which was further decreased to 95.22 ng/μl, 98.22 ng/μl, and 132.88 ng/μl, respectively, following SKP intervention (P < 0.001). However, Group III had a higher HBD-2 level at 90th day as compared to other groups. Conclusion: There was an improvement in PI and GI with a decrease in salivary HBD-2 in chronic periodontitis patients following SKP. Hence, SKP can be considered as an adjunct to treatment modality in patients with periodontal disease.